Survival analysis of patients with chondrosarcomas of the pelvis. Issue 1 (16th May 2013) - Mavrogenis, Andreas F.; Angelini, Andrea; Drago, Gabriele; Merlino, Biagio; Ruggieri, Pietro
Abstract Background Studies for patients with pelvic chondrosarcomas are limited. This study determines the outcome of patients with pelvic chondrosarcomas, and whether there is any association with tumors' grade, type, stage, margins and pelvic location. Materials and Methods We retrospectively studied 215 patients with pelvic chondrosarcomas. All patients had biopsy and histological diagnosis of their tumors followed by limb salvage or amputation. We staged patients using the Musculoskeletal Tumor Society system. We performed a univariate and multivariate analysis of the survival to death, local recurrence and metastasis with respect to grade, type (central vs. peripheral), stage, margins, and pelvic location, and the survival to death of patients with and without local recurrence. Results Grade was the most important univariate and multivariate predictor of the survival of the patients. Dedifferentiation was associated with significantly lower overall survival. Peripheral chondrosarcomas predicted survival only in the univariate analysis. Surgical margins predicted local recurrence only in the multivariate analysis. Periacetabular location was associated with lower survival to death and local recurrence. The occurrence of local recurrence compromises the overall survival. Conclusion Grade was the most important predictor of the overall survival of patients with chondrosarcomas of the pelvis. J. Surg. Oncol. 2013 108:19–27. © 2013 Wiley Periodicals, Inc.